Pelatihan Pembuatan Hampres Sebagai Peluang Usaha di Pasar Johar Semarang - Silvia Dirgahayu; Mitha Ardhian K; Anandita Pratiwi; Anisa Wahyu Anggreani; Ardan Cetta Anugraha (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This Hampers Making Training aims to improve entrepreneurial abilities in making various gifts, hampers, parcels, various gifts and balloon bouquets. This activity was held at the South Johar Market, Semarang City, with 21 mothers and young men and women participating. The aim of this training is to increase entrepreneurial interest in the creative economy sector in making gifts and various gifts among women, as well as supporting women's empowerment programs. This training provides the skills needed to make various deliveries, hampers, parcels, various gifts and balloon bouquets, as well as increasing the awareness and ability of entrepreneurs in developing their businesses. The results of this training show that entrepreneurs who take part in this training have better abilities in making various deliveries and various gifts, and have higher motivation to develop their businesses.